2015
DOI: 10.1186/s12891-015-0629-8
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent idiopathic scoliosis without limb weakness: a differential diagnosis of core myopathy?

Abstract: BackgroundCore myopathies are a clinically and genetically heterogeneous group of congenital myopathies with the common defined histopathological feature of focally reduced oxidative activity on muscle biopsy. It has a low incidence, however, recent articles show broad clinical spectrum, suggesting that the real incidence should be considerably larger than previously described. Due to the important association between scoliosis and paravertebral muscle imbalance, numerous authors study, by biopsy of the spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In addition, atrophy, and core presence, also occur in these muscles in patients with AIS. However, there is disparity in the literature as to whether these changes are the cause or an effect of the deformity (Chagas et al, 1993;Meier et al, 1997;Luciano et al, 2015;Wajchenberg et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, atrophy, and core presence, also occur in these muscles in patients with AIS. However, there is disparity in the literature as to whether these changes are the cause or an effect of the deformity (Chagas et al, 1993;Meier et al, 1997;Luciano et al, 2015;Wajchenberg et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…39 Congenital myopathies, although rare and non-progressive, can also cause scoliosis over the years. 40…”
Section: G) Other Conditionsmentioning
confidence: 99%
“…Moth-eaten bers were indicated by the aky and irregular loss of oxidase in staining, and could be present near the center or the edge of muscle bers. Their presence near the center of muscle bers could resemble the presentation of core myopathy, and must be differentiated by clinical manifestations and genetics (7,8). Furthermore, patients with severe scoliosis tended to have more NADH de ciency than patients with mild scoliosis (P = 0.053, although there was no statistically signi cant difference), suggesting the metabolic dysfunction of myo bers.…”
Section: Paraspinal Muscle Atrophy and Degenerationmentioning
confidence: 99%
“…According to the previous literature, AIS is often accompanied by certain but unspeci ed pathological changes in paraspinal nerves or muscles (7). In 2015, Luciano et al (8) reported cases of AIS patients who didn't show the typical symptoms of decreased limb muscle strength and of limited respiratory muscle function; however, the results of the paraspinal muscle biopsies of two patients with AIS indicated a high likelihood of core myopathy, but the patients did not develop core myopathy eventually. A hypothetical explanation is that this sort of AIS patients may be a special manifestation of the core myopathy.…”
Section: Introductionmentioning
confidence: 99%